Pendidikan Kesehatan Gigi Untuk Menciptakan Generasi Sehat Pada Anak Di Mdt Al Hidayah Desa Sumber Sari, Kecamatan Kabawetan, Kabupaten Kepahiang - Zella Tantionika; Agustin , Melly; Situmorang , Anggita; Fernandes , Brilian; Murwati, Murwati; Azissah, Danur; Wulandari, Wulandari; Rohani, Tuti (Jurnal Kewirausahaan dan Bisnis, 2025)
Oral health is one of the factors that not only affects the oral cavity and masticatory function, but can directly affect quality of life. Dental health that is well maintained from an early age can affect behavior and development later in life (Kamran et al, 2014).Objectives: At the end of the counseling process, all children at MDT AL HIDAYAH Sumber Sari Village, Kebawetan Kec Kepahiang Kab, can understand and understand about dental hygiene. Methods: The method used in this counseling is by delivering material using PPT, Animated Video, and leaflets. Results and discussion: The final result of this activity, the extension worker is able to provide counseling material that has been made at least 90% of the counseling material.